2012
DOI: 10.1155/2012/598984
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Studies Performed in the Ecuadorian Population

Abstract: Genotoxicity studies in Ecuador have been carried out during the past two decades. The focuses of the research were mainly the area of environmental issues, where the populations have been accidentally exposed to contaminants and the area of occupational exposure of individuals at the workplace. This paper includes studies carried out in the population of the Amazon region, a zone known for its rich biodiversity as well as for the ecological damage caused by oil spills and chemical sprayings whose consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…The proband and her parents had Giemsa trypsin banding (GTG) technique. 22 Chromosomal analysis of the proband showed that chromosome 14 had an extra segment attached, 46,XX,add (14) Fig. S2, available in the online version).…”
Section: Cytogenetic Assessment Of Proband and Parentsmentioning
confidence: 99%
“…The proband and her parents had Giemsa trypsin banding (GTG) technique. 22 Chromosomal analysis of the proband showed that chromosome 14 had an extra segment attached, 46,XX,add (14) Fig. S2, available in the online version).…”
Section: Cytogenetic Assessment Of Proband and Parentsmentioning
confidence: 99%
“…Chromosome segregation during gametogenesis or mitosis during early fetal development, maternal age and environmental factors increase the risk of chromosomal abnormalities (Kim, Lee, Kim, Shim, & Cha, 2013;Mohammed, Shawky, Soliman, & Ahmed, 2011;Moorthie et al, 2017). Particularly, Ecuadorian population has adapted to live at high-altitude, besides being exposed to high UV radiation levels and other genotoxic agents (Paz-y-Miño, Cumbal, & Sánchez, 2012b;Paz-y-Miño, Guillen Sacoto, & Leone, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As cigarette smoke contains numerous carcinogens including polycyclic aromatic hydrocarbons (PAH), aromatic amines and N-nitroso compounds, as well as reactive oxygen species (ROS) which are responsible for the DNA damages like chemical change of bases, single-strand breaks (SSBs), double strand breaks (DSBs) and finally lead to genomic instability and drive the tumor phenotype [9][10][11][12][13][14]. Besides, BC is substantially increased by carcinogen exposed people especially due to xenobiotic metabolizing enzyme polymorphism for example tumor protein 53 (TP53), N-acetyl transferase 2 (NAT2), glutathione S-transferase P1 (GSTP1) and human 8-oxoguanine DNA glycosylase 1 (OGG1) polymorphism [5,[15][16][17]. Thus, it is important to detect the DNA damage in different geographic region population due to their distinctive combination of polymorphic traits which may alter genetic susceptibility as well as response to drugs, chemicals, and carcinogens.…”
Section: Introductionmentioning
confidence: 99%